Pengelompokkan Kondisi Fisik Cabang Olahraga Berdasarkan Daya Tahan Otot Tungkai dan VO2max Menggunakan Metode Single Linkage - Ihsani, Sri Indah; Anugrah, Sendy Mohamad; Mulyawan, Rizky; Kurniawan, Dennis Dwi (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
The gathering of athletes' physical condition items, specifically leg muscle endurance and cardiorespiratory endurance (VO2max) in a variety of sports at the regional training facility in Banten Province is crucial for training based on leg muscle endurance and VO2Max. Methods: This quantitative descriptive study employs the single linkage approach to examine 119 athletes from 25 different sports in Serang, Banten. One-hour data retrieval of leg muscular endurance using the Hurdle Jump test and VO2Max using the Beep test. Data analysis with R-studio. Results: Based on the results of grouping using the single link method, the following can be stated: (1) Cluster 1 consists of six sports, including Kite Flying, Hanging, Aeromodelling, Paragliding, Rugby, and Motorized (Vo2 max and low endurance); (2) Cluster 2 consists of nine sports, including Taekwondo, Baseball, Cricket, Softball, Tarung Derajat, Kempo, Basketball, Sailing, and Karate. Cluster 3 is comprised of four sports: Athletics (Jumping), Pencak Silat, Hockey, and Badminton. (4) Cluster 4 comprises six sports, including Sepak Takraw, Judo, Roller Skating, Wushu, Wrestling, and Athletics, as representatives of the grouping of sports in the Serang region of Banten. Conclusion: the need for greater muscle endurance and fitness is directly related to the intensity of aerobic exercise. But not vice versa, because sports have different characteristics, even though cardiovascular fitness is the most important factor in supporting players' physical talents.